2010
DOI: 10.2967/jnumed.110.075960
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Posttherapy 131I SPECT/CT on Risk Classification and Management of Patients with Differentiated Thyroid Cancer

Abstract: The objective of this study was to determine whether posttherapy 131 I SPECT/CT changed the need for additional crosssectional imaging or modified the American Thyroid Association risk of recurrence classification. We performed planar imaging and SPECT/CT in a consecutive series of patients after 131 I therapy. Methods: Planar imaging and SPECT/CT were performed on 148 consecutive patients with thyroid carcinoma (125 papillary, 2 follicular, 8 Hü rthle cell, and 13 poorly differentiated) approximately 5 d afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 14 publications
7
59
0
8
Order By: Relevance
“…In all patients free of disease at follow-up evaluations, initial postablative SPECT/CT was negative or equivocal for disease. However, SPECT/CT was positive for disease in 78% of patients identified with persistent or recurrent disease at follow-up; the fact that post-therapy WBS was negative in 22% patients with persistent or recurrent disease during follow-up points to the presence of non-iodine-avid metastases, also reported by other groups in 20%-30% of patients (36,48). The authors conclude that postablation scintigraphy (planar WBS and SPECT/CT) has 78% sensitivity and 100% specificity for predicting recurrent or persistent disease and is the sole independent prognostic variable for disease-free survival (49).…”
Section: Utility Of Post-therapy Radioiodine Spect/ctmentioning
confidence: 60%
See 1 more Smart Citation
“…In all patients free of disease at follow-up evaluations, initial postablative SPECT/CT was negative or equivocal for disease. However, SPECT/CT was positive for disease in 78% of patients identified with persistent or recurrent disease at follow-up; the fact that post-therapy WBS was negative in 22% patients with persistent or recurrent disease during follow-up points to the presence of non-iodine-avid metastases, also reported by other groups in 20%-30% of patients (36,48). The authors conclude that postablation scintigraphy (planar WBS and SPECT/CT) has 78% sensitivity and 100% specificity for predicting recurrent or persistent disease and is the sole independent prognostic variable for disease-free survival (49).…”
Section: Utility Of Post-therapy Radioiodine Spect/ctmentioning
confidence: 60%
“…Based on SPECT/CT findings, ATA risk classification changed in 7 of 109 patients (6.4%). Importantly, review of the CT data of the SPECT/CT study identified non-iodine-avid metastases in 32 of 148 patients (22%) and demonstrated that the size of nodal metastases can be measured on the CT component of SPECT/CT; additional imaging studies were avoided in 48% of patients (48).…”
Section: Utility Of Post-therapy Radioiodine Spect/ctmentioning
confidence: 99%
“…In postablation setting, neck and thorax SPECT-CT improves the N staging of patients with DTC (4,9). SPECT-CT data may also reduce the need for additional cross-sectional imaging in 20% of patients and alter the ATA risk of recurrence classification in 6% of patients (10). In a primary report, we demonstrated that a positive postablation SPECT-CT predicted treatment failure at 2 years better than a positive WBS (3).…”
Section: Discussionmentioning
confidence: 82%
“…Сцинтиграфия всего тела [205][206][207][208][209][210][211][212][213][214][215][216] Рекомендация 42. У пациентов с био-химической ремиссией после РЙТ проведе-ние плановой СВТ не показано.…”
Section: определение тиреоглобулина и антител к тиреоглобулинуunclassified